Keratoacanthoma, committed stem cells and neoplastic aberrant infundibulogenesis integral to formulating a conceptual model for an infundibulocystic pathway to squamous cell carcinoma. (16th October 2020) - Kossard, Steven
Abstract: Keratoacanthomas (KAs) are distinctive tumors that are defined by their clinical and histopathological features. Their relationship and distinction from squamous cell carcinoma (SCC), however, remain controversial. All cytogenic and immunohistochemical markers that have been applied in this quest have failed. A close relationship of KAs to hair follicles has been recognized. The descriptive term infundibulocystic or infundibular SCC was introduced to define a more broad‐based pathway encompassing KAs. The follicular infundibulum roles in respect to neoplasia and wound healing are important elements in understanding the pathogenesis of KAs. Mouse models for KA have provided insights into the relationship of KA to follicles and SCCs. These advances and together with the diverse clinical and histopathological aspects of KA have contributed to the formulation of a conceptual pathway. The central element is that ultraviolet (UV)‐mutated or activated committed infundibular stem cells are driven by the combination of a mutated oncogenic RAS pathway linked with the Wnt/beta‐catenin pathway responsible for stem cell maintenance, hair follicle development, wound healing and driving KA proliferation and terminal keratinization. The existence and activation of this mutated pathway may form the basis of the paradoxical emergence of KAs and SCCs in patients receiving BRAF and PD‐1 inhibitor therapy.